MEMAKNAI CREATIVE ACCOUNTING DENGAN KEINDAHAN NILAI-NILAI KEARIFAN LOKAL SIRI’ NA PACCE - Nurwanah, Andi; Hanafie, Hadriana (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2019)
Understanding creative accounting with the beauty of local wisdom values siri’ na pacce. This study aims to interpret the cultural wisdom of Bugis_Makassar siri’ na pacce in the relationship of creative accounting. Through case studies, researchers explored the role of culture in shaping its reality. The results of this study found that accountants cling to local wisdom values of siri’ na pacce. Have high self-esteem, feel ashamed when doing dishonest deeds. The value has five principles: There are tongeng (say true), lempu (honesty), getteng (cling to prinsive belief), sipakatau (mutual respect) and mappisona ri Dewata Seuwwae (resigned to the power of god almighty).